2022
DOI: 10.4337/ejeep.2022.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of capitalism to enforce ecologically sustainable GDP growth: lessons from Keynes and Schumpeter

Hansjörg Herr

Abstract: An economy with a low stable medium-term growth rate given by ecological needs is only possible after a radical reform of the type of capitalism we have today. In an ecologically sustainable economic system, aggregate demand has to be controlled on a macroeconomic level. Of focal importance is the steering of investment. Here a national credit plan that fixes the national credit volume and to a certain extent the allocation of credit is in the centre. For consumption demand in a low-growth economy it is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A is the cost of the loan to make the intermediate product. It can be viewed as the lending rate of commercial banks [7]. From the perspective of the first hypothesis, it can be concluded that in the first case, the supply of the intermediate production firm and the profit of the monopoly is:…”
Section: Intermediate Product Departmentmentioning
confidence: 99%
“…A is the cost of the loan to make the intermediate product. It can be viewed as the lending rate of commercial banks [7]. From the perspective of the first hypothesis, it can be concluded that in the first case, the supply of the intermediate production firm and the profit of the monopoly is:…”
Section: Intermediate Product Departmentmentioning
confidence: 99%